Report of the Managing Director to the International Monetary and Financial Committee on a New Income and Expenditure Framework for the International Monetary Fund. (Policy Papers; Policy Paper ;, 2008)
The October 2007 Communique of the IMFC called on the Executive Board to develop specific proposals on a new income model and a new expenditure framework by the time of the 2008 Spring Meetings. On April 7, 2008, the Executive Board endorsed a new income model for the Fund and considered a new medium-term budgetary envelope for financial years 2009-11, which includes deep spending cuts, and approved administrative, restructuring, and capital budgets for financial year 2009. As a key element of this new income-expenditure framework, the Executive Board ecommended the adoption by the Board of Governors of an amendment of the Articles of Agreement to expand the Fund's investment authority. The Executive Board's recommendation was sent to the Board of Governors, with the voting period running through 6:00 pagesm., Washington time, May 5, 2008.